Perceptions and Understanding of Organ Donation Among Medical Undergraduates in Southeastern Nigeria - Njelita, Ifeoma Anne; Akabuike, Josephat Chukwudi; Eyisi, Ifeanyi Gabriel; Nwachukwu, Chinyerem Cynthia; Ezenyeaku, Chijioke Amara; Ezeonyejiaku, Nonye Juliana; Mbomson, Onyinye Paschaline (Scripta Medica, 2025)
Background/Aim: Organ donation continues to be acknowledged globally as the preferred treatment for individuals with end-stage organ diseases. So far, it is one of the greatest advances of modern science and has resulted in many patients getting a new lease of life. This research focused on assessing the understanding and perspectives of undergraduate medical students regarding organ donation.Methods: This descriptive survey was conducted among the undergraduate medical students at a government University in Anambra State of Nigeria. Data on knowledge and attitude were collected from the respondents using self-administered pre-tested questionnaires. Result: More than 95 % of the participants demonstrated awareness of organ donation. Majority (43.4 %) identified a healthy living donor as an ideal candidate for organ donation. Participants who were clinical students were predominantly aware that the donor and recipient's blood groups must be compatible, as well as their human leukocyte antigens (HLA) being identical (OR = 2.2 and 2.5, respectively). They were also predominantly willing to donate their organs after death and to encourage their future patients to donate their organs (OR = 7.88 and 5.49, respectively). Pre-clinical students tended to agree more with the idea of keeping their bodies intact after death. (OR = 6.41). Conclusion: Organ donation should be given greater emphasis and introduced early in the medical curriculum. This will serve to improve knowledge and bring about a desirable attitudinal change among future medical practitioners.